Alisol A inhibits and stabilizes atherosclerotic plaques by protecting vascular endothelial cells - Ma, Yang; Song, Dingzhong; Yuan, Jie; Hao, Wusi; Xi, Jianqiang; Yuan, Chunping; Cheng, Zhihong (Frontiers in Pharmacology, 2024)
Background and aims: Dysfunction of endothelial cells represents a crucial aspect in the pathogenesis of atherosclerosis. The aim of this study was to explore the protective effects of alisol A on vascular endothelial cells and its possible mechanisms. Methods: An atherosclerosis model was established by feeding ApoE-/-mice with high-fat chow. Alisol A (150 mg/kg/d) or atorvastatin (15 mg/kg/d) was administered, and the levels of blood lipids were evaluated. The effect of the drugs on atherosclerotic plaques was observed by staining the aorta with Sudan IV. In vitro experiments were conducted using human aortic endothelial cells (HAECs) to assess the effects of alisol A on cell proliferation, migration, tubulation, secretion, and cellular integrity by CCK-8 assay, wound healing assay, angiogenesis assay, NO secretion, and release of LDH. Transcriptomics and molecular docking were used to explore the mechanism of plaque inhibition and stabilization by alisol A. Results: Alisol A significantly reduced the aortic plaque area in ApoE -/-mice fed with high-fat chow . In vitro, alisol A had a protective effect on HAECs, which was reflected in the inhibition of vascular endothelial cell proliferation, promotion of NO secretion by vascular endothelial cells, inhibition of vascular endothelial cell migration and angiogenesis, and the maintenance of cell membrane integrity. Therefore, alisol A inhibited and stabilized atherosclerotic plaques and slowed down the process of atherosclerosis. Transcriptomics studies showed 4086 differentially expressed genes (DEGs) in vascular endothelial cells after alisol A treatment. Enrichment analysis indicated that many genes involved in TNF signaling pathway were differentially expressed, and inflammatory genes were suppressed. The molecular docking results verified the hypothesis that alisol A has a low binding energy after docking with TNF target, and TNF could be a potential target of alisol A. Conclusions: Alisol A produced protection on vascular endothelial cells, achieving inhibition and stabilization of atherosclerotic plaques.